Effect of Concentration and Frequency of Giving PKS Liquid Waste on Growth and Products of Palm Plants (Brassica juncea L.): Pengaruh Konsentrasi dan Frekuensi Pemberian Limbah Cair PKS Terhadap Pertumbuhan dan Hasil Tanaman Sawi (Brassica Juncea L.) - Nora Julita Nora Julita; Chairudin Chairudin (Agrifarm : Jurnal Ilmu Pertanian, 2022)
Research on the effect of concentration and frequency of giving PKS liquid waste on the growth and yield of mustard (Brassica juncea L.) was conducted in Arongan Village, Kuala Pesisir District, Nagan Raya Regency starting from November to December 2021. The design used was a randomized block design (RAK) factorial. The first factor is the concentration of PKS liquid waste which consists of 3 treatment levels K1 (4%), K2 (8%), and K3 concentration of PKS liquid waste 12%). The second factor is the frequency of watering PKS liquid waste which consists of 3 levels of treatment P1(frequency of watering PKS liquid waste 5 days 1 time), P2 (frequency of watering PKS liquid waste 7 days 1 time), and P3 (frequency of watering PKS liquid waste 9 days). 1 time). The results of the study did not show an interaction between the treatment of PKS liquid waste concentration and the frequency of watering PKS liquid waste with all observed variables. The concentration of PKS liquid waste had a significant effect on the number of leaves at 29 DAP and root length. Varieties treatment did not have a significant effect on all observed variables. Keywords: concentration, frequency, PKS liquid waste, mustard plant